KIDNEY CYST WITH NEPHROLITHIASIS AND CYSTITIS - Rendy Maulana Imron (PT. Hasba Edukasi Mandiri, 2025)
Kidney cysts, nephrolithiasis, and cystitis are common conditions that can significantly affect the urinary system, especially in elderly patients. These conditions often present with overlapping symptoms such as frequent urination, hematuria, and dysuria, making diagnosis and treatment challenging. Kidney cysts, particularly large ones, can cause urinary disturbances and increase the risk of stone formation, while nephrolithiasis can lead to pain and obstruction in the urinary tract. Cystitis, an inflammation of the bladder, can further exacerbate these symptoms. This article discusses the pathophysiology, differential diagnosis, and management strategies for these conditions, emphasizing the importance of early diagnosis through imaging and the role of lifestyle modifications such as fluid intake and dietary adjustments. Tailored treatment plans that consider the patient's age, comorbidities, and overall health are essential for effective management and improving the patient's quality of life.